Not Yet a Woman: The Influence of Socio-Political Constructions of Motherhood on Experiences of Female Infertility. (24th June 2019) - Wells, Hannah; Heinsch, Milena
Abstract: In contemporary pronatalist societies, motherhood and childbearing are constructed as inevitable fulfilments of the female identity, resulting in the stigmatisation of women who do not conform to these feminine 'ideals'. This article reports on the findings of a scoping review, which explored constructions of women and motherhood in Western societies, and how they influence women's experiences of infertility. Three key themes were identified: (i) the 'women as mothers' discourse; (ii) medicalisation and the 'female biological fault'; and (iii) 'deviant' mothers and infertility. While these themes facilitate a deeper understanding of the ways social ideologies can influence the identity and life-course of infertile women, the current literature was found to be overwhelmingly medical in focus, centred on the concept of Assisted Reproductive Technologies. This article aims to expand narrow discourses on female infertility by exploring women's support needs and the socio-political impacts on their experience. It extends the interdisciplinary knowledge base in this area by considering the contributions social work can make in addressing these systemic factors.